International Humanitarian Cooperation: Foreign Approaches to Studying and Realisation - K. M. Tabarintseva-Romanova (Сравнительная политика)
The article is studying foreign approaches to the interpretation and realization of international humanitarian cooperation. Humanitarian cooperation is becoming one of the effective mechanisms of foreign policy infl uence. Its interpretation itself sounds differently in Russian and foreign research. At the beginning of the article, the author considers the methodological foundations of the study, namely, based on academic publications of foreign researchers involved in the development of the concept of humanitarian / cultural cooperation, a brief description of humanitarian cooperation is given, with its defi nition and transformation of the meaning of the term. Further, the author identifi es the following approaches to the defi nition and realization of humanitarian cooperation in foreign political and diplomatic practice: universal, regional, statist. Based on the analysis of documents of international organizations (UNESCO, Council of Europe, European Union, ASEAN, African Union, etc.), as well as of several countries (France, Italy, USA), the main approaches to the study and realization of this type of interstate interaction are highlighted. The choice of countries is determined by the fact that they possess offi cially published documents regarding their international humanitarian cooperation strategy. In addition, France is a “pioneer” in the formation of a united European cultural policy; 40 % of UNESCO's cultural heritage sites are concentrated in Italy; the USA is a theoretical and methodological pioneer of the concept of “soft power” and public diplomacy, with which humanitarian cooperation is inextricably linked. The article concludes that in international discourse, humanitarian cooperation is one of the effective tools of “soft power” and includes such areas as: culture, science, education, sports, youth issues, which is more consistent with the Russian interpretation of this type of international interaction, but at the same time, the international discourse uses the concept of “cultural cooperation” in the majority of cases to determine such interaction. In conclusion, the author's classifi cation of foreign approaches to international humanitarian cooperation is proposed.